A Medical Manipulator System with Lasers in Photodynamic Therapy of Port Wine Stains. (14th August 2014) - Wang, Xingtao; Tian, Chunlai; Duan, Xingguang; Gu, Ying; Huang, Naiyan
Abstract : Port wine stains (PWS) are a congenital malformation and dilation of the superficial dermal capillary. Photodynamic therapy (PDT) with lasers is an effective treatment of PWS with good results. However, because the laser density is uneven and nonuniform, the treatment is carried out manually by a doctor thus providing little accuracy. Additionally, since the treatment of a single lesion can take between 30 and 60 minutes, the doctor can become fatigued after only a few applications. To assist the medical staff with this treatment method, a medical manipulator system (MMS) was built to operate the lasers. The manipulator holds the laser fiber and, using a combination of active and passive joints, the fiber can be operated automatically. In addition to the control input from the doctor over a human-computer interface, information from a binocular vision system is used to guide and supervise the operation. Clinical results are compared in nonparametric values between treatments with and without the use of the MMS. The MMS, which can significantly reduce the workload of doctors and improve the uniformity of laser irradiation, was safely and helpfully applied in PDT treatment of PWS with good therapeutic results.